Study on the Development Path of Liaoning Province’s REITs Business Under the Background of Financial Innovation - Hu, Jin (Journal of Global Economy, Business and Finance, 2025)
Guided by policies such as the “Notice on Comprehensively Promoting the Regular Issuance of Infrastructure Real Estate Investment Trusts (REITs) Projects”, and in combination with the development practice of REITs in Liaoning Province, this paper analyzes the necessity and feasibility of the development of REITs business in the province under the background of financial innovation. By sorting out the asset base and practical cases of cities such as Shenyang and Dalian, it is found that Liaoning Province has inherent advantages in areas such as industrial parks and public rental housing, but there are problems such as insufficient operational capacity and lagging asset integration. The research suggests that a development path should be constructed from aspects such as the cultivation of assets in multiple fields, the upgrading of operation models, and the improvement of policy mechanisms, to provide financial support for activating the existing assets in Liaoning and promoting the revitalization of Northeast China.